Neodymium Isotope Geochemistry of a Subterranean Estuary - Chevis, Darren A.; Mohajerin, T. Jade; Yang, Ningfang; Cable, Jaye E.; Rasbury, E. Troy; Hemming, Sidney R.; Burdige, David J.; Martin, Jonathan B.; White, Christopher D.; Johannesson, Karen H. (Frontiers in Water, 2021)
Rare earth element (REE) and Nd isotope compositions of surface and groundwaters from the Indian River Lagoon in Florida were measured to investigate the influence of submarine groundwater discharge (SGD) on these parameters in coastal waters. The Nd flux of the terrestrial component of SGD is around 0.7±0.03 μmol Nd/day per m of shoreline across the nearshore seepage face of the subterranean estuary. This translates to a terrestrial SGD Nd flux of 4±0.2 mmol/day for the entire 5880 m long shoreline of the studied portion of the lagoon. The Nd flux from bioirrigation across the nearshore seepage face is 1±0.05 μmol Nd/day per m of shoreline, or 6±0.3 mmol/day for the entire shoreline. The combination of these two SGD fluxes is the same as the local, effective river water flux of Nd to the lagoon of 12.7±5.3 mmol/day. Using a similar approach, the marine-sourced SGD flux of Nd is 31.4±1.6 μmol Nd/day per m of shoreline, or 184±9.2 mmol/day for the investigated portion of the lagoon, which is 45 times higher than the terrestrial SGD Nd flux. Terrestrial-sourced SGD has an εNd(0) value of -5±0.42, which is similar to carbonate rocks (i.e., Ocala Limestone) from the Upper Floridan Aquifer ( -5.6), but more radiogenic than the recirculated marine SGD, for which εNd(0) is -7±0.24. Marine SGD has a Nd isotope composition that is identical to the εNd(0) of Fe(III) oxide/oxyhydroxide coated sands of the surficial aquifer (-7.15±0.24 and -6.98±0.36). These secondary Fe(III) oxides/oxyhydroxides formed during subaerial weathering when sea level was substantially lower during the last glacial maximum. Subsequent flooding of these surficial sands by rising sea level followed by reductive dissolution of the Fe(III) oxide/oxyhydroxide coatings can explain the Nd isotope composition of the marine SGD component. Surficial waters of the Indian River Lagoon have an εNd(0) of -6.47±0.32, and are a mixture of terrestrial and marine SGD components, as well as the local rivers (-8.63 and -8.14). Nonetheless, the chief Nd source is marine SGD that has reacted with Fe(III) oxide/oxyhydroxide coatings on the surficial aquifer sands of the subterranean estuary.